Phytomedicinal Knowledge and “Official” Sources in Tatev (Armenia) - Hovsepyan, Roman; Stepanyan-Gandilyan, Nina; Stollberg, Christian (Ethnobiology Letters, 2019)
Ethnographic investigations in the villages of the Tatev community in southern Armenia reveal the positive attitude of the local community toward “official” sources (e.g., printed books, administrative officials, and people of higher education) on herbal medicine and the belittling of their own traditional ethnobotanical knowledge. Although this may be a global phenomenon, we observe and discuss particular reasons specific to the post-Soviet context as conditioned by politics and propaganda. Nowadays, the local population gather and use a minimum of forty wild plants (ethnotaxa) mostly for nutritional, medicinal, and aromatic (tea and flavoring) purposes. Biological species of the traditionally used medicinal plants of the Tatev community were identified, and preparation methods and purposes of the herbal remedies were recorded. The most frequently and traditionally used medicinal plants of the Tatev community belong to these genera: Mentha, Thymus, Ziziphora, Hypericum, Knautia, Arctium, Plantago, Tanacetum, Rosa, and Sambucus.